Measurement and Analysis of Target Strength of Tiger Grouper Fish (Epinephelus fuscoguttatus) Using Acoustic Methods in Lancang Island Seawater - Agustina Sartika Yos Ekaristi Manik; Henry Munandar Manik; Totok Hestirianoto (Politeknik Negeri Batam, 2022)
Coral fish are organisms with the largest amount of biomass and are also large organisms that can be found in coral reef ecosystems. The tendency of coral fish is that they do not move around and are always in a certain area and are very relocated although still many (Nybakken, 1988). The coral fish that are often found on the island of Lancang is the Tiger Grouper fish (Epinepheus fuscoguttatus). Grouper fish have a high economic value if fishermen do good cultivation on this Lancang island. The method used was mobile and controlled hydroacoustics, located in Pulu Lancang Thousand Islands. The instruments used are SIMRAD EK 15. The number of samples measured as many as 3 heads with a total length ranging from 21,70 cm to 42,50 cm and has the total weight of the three fish of 186,9 gr to 640 gr with a recording time of 5 minutes was done at the Dock and Floating Net Cage. The sounding results of tiger grouper were then analyzed using Echoview 4.0 and microsoft excel. The results of the analysis showed the average TS value in 3 tiger groupers whose total length ranged from -34,77 dB to -32,37 dB and the longer the total length of the fish, the greater the TS value.